Use of the evidence base in substance abuse treatment programs for American Indians and Alaska natives: pursuing quality in the crucible of practice and policy - Novins, Douglas K (BioMed Central, 2011)
BACKGROUND: A variety of forces are now shaping a passionate debate regarding the optimal approaches to improving the quality of substance abuse services for American Indian and Alaska Native communities. While there have been some highly successful efforts to meld the traditions of American Indian and Alaska Native tribes with that of 12-step approaches, some American Indian and Alaska Natives remain profoundly uncomfortable with the dominance of this Euro-American approach to substance abuse treatment in their communities. This longstanding tension has now been complicated by the emergence of a number of evidence-based treatments that, while holding promise for improving treatment for American Indian and Alaska Natives with substance use problems, may conflict with both American Indian and Alaska Native and 12-step healing traditions. DISCUSSION: We convened a panel of experts from American Indian and Alaska Native communities, substance abuse treatment programs serving these communities, and researchers to discuss and analyze these controversies in preparation for a national study of American Indian and Alaska Native substance abuse services. While the panel identified programs that are using evidence-based treatments, members still voiced concerns about the cultural appropriateness of many evidence-based treatments as well as the lack of guidance on how to adapt them for use with American Indians and Alaska Natives. The panel concluded that the efforts of federal and state policymakers to promote the use of evidence-based treatments are further complicating an already-contentious debate within American Indian and Alaska Native communities on how to provide effective substance abuse services. This external pressure to utilize evidence-based treatments is particularly problematic given American Indian and Alaska Native communities' concerns about protecting their sovereign status. SUMMARY: Broadening this conversation beyond its primary focus on the use of evidence-based treatments to other salient issues such as building the necessary research evidence (including incorporating American Indian and Alaska Native cultural values into clinical practice) and developing the human and infrastructural resources to support the use of this evidence may be far more effective for advancing efforts to improve substance abuse services for American Indian and Alaska Native communities.